Praktek Penggunaan Alat Pelindung Diri (APD) dan Keselamatan Kerja Mahasiswa di Laboratorium Keperawatan, Poltekkes Tanjungpinang : The Practice of Using Personal Protective Equipment (PPE) and Student Work Safety in Nursing Laboratories, Tanjungpinang Health Polytechnic - Yas Suriani; Santa Novita Yosephin Silalahi (Poltekes Kemenkes Tanjungpinang, 2022)
There were several incidents of work accidents in the form of needle sticks recorded in several studies in Indonesia from 2014-2021, totaling 57 cases. Potential hazards in educational laboratories are considered lower than in health laboratories and industrial laboratories because they use relatively fewer materials. However, it will still result in financial losses, injuries and damage to equipment and infrastructure. Based on the results of interviews with the head of the nursing laboratory sub-unit, it was found that some students did not wear PPE (Personal Protective Equipment) during the practicum. In 2019 there were 2 incidents of students getting needle sticks during practice. There were 3 students who did not wear full PPE when the practicum took place in 2022. Compliance with the use of PPE at the Tanjungpinang Health Polytechnic Nursing Laboratory during the practicum greatly affects the personal safety of the students themselves. This study aimed to determine the practice of using PPE on student work safety in the nursing laboratory. The researcher involved all students of the second semester of Nursing Study Program for the 2021-2022 academic year and were willing to be involved in research. The number of respondents as many as 78 people. Data were obtained through a questionnaire in the form of a test sheet containing 30 questions. The results of data analysis showed that 55% of respondents had high knowledge of the use of PPE and as many as 46% had a positive attitude in using PPE and 54% had a negative attitude. Students are required to read laboratory rules and provide sanctions to students who do not comply with the use of PPE in the laboratory.